Studies in New Testament and early Christian literature essays in honor of Allen P. Wikgren - Aune, David Edward (Leiden Brill, 1972)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. -- criticism, interpretation, etc; Early Christian literature -- criticism, interpretation, etc